Prognosis of knee joint osteoarthrosis progression - Korzh, Mykola; Golovakha, Maksim; Gavrilenko, Boris; Aghaev, Emin; Schabus, Rudolf; Orljanski, Weniamin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The factors, which affect the course of knee osteoarthrosis, are mostly unknown by now. The presence of bone tissue lesions, revealed during MRI, and deviations of the leg mechanical axis are known clinical-radiological criteria, considered by a number of authors as risk factors for the beginning of progression of knee joint osteoarthrosis. The purpose of the work: to determine whether the appearance of a subchondral bone-tissue oedema on MRI is a prognostically significant criterion of knee joint osteoarthrosis progression or the latter does not depend upon this process and is caused by a deviation of the extremity axis. Methods of examination: MRI and radiography of the knee joint. Osteoarthrosis progression was assessed by a narrowing of the joint space and changes in the mechanical axis of the extremity. The clinical material consisted of 211 patients with gonarthrosis, aged 43-64, 160 (76 %) of them being examined at least twice. Medial bone-tissue oedemata on MRI were observed mostly in patients with varus deviations of the mechanical axis, lateral bone-tissue oedemata were common in patients with valgus knee joint deformities. Of 106 patients with a bone-tissue oedema in the medial part, osteoarthrosis progression was found in 42 (39.6 %) cases, while 54 patients without any bone-tissue oedema developed some progression of the process only in 5 (9.3 %) cases. Approximately 69 % of patients with a subchondral bone-tissue oedema in the medial part of their knee joints revealed a varus deviation of the mechanical axis of the knee joint. Conclusion: a subchondral bone-tissue oedema is a considerable risk factor for an aggravation of the structural-functional state of the knee joint in osteoarthrosis, a disturbance in the extremity axis being statistically related with this process only in part.